Difference Within and Without: Health Care Providers' Engagement With Disability Arts. (July 2019) - Viscardis, Katharine; Rice, Carla; Pileggi, Victoria; Underhill, Angela; Chandler, Eliza; Changfoot, Nadine; Montgomery, Phyllis; Mykitiuk, Roxanne
ReVision, an assemblage of multimedia storytelling and arts-based research projects, works creatively and collaboratively with misrepresented communities to advance social well-being, inclusion, and justice. Drawing from videos created by health care providers in disability artist-led workshops, this article investigates the potential of disability arts to disrupt dominant conceptions of disability and invulnerable embodiments, and proliferate new representations of bodymind difference in health care. In exploring, remembering, and developing ideas related to their experiences with and assumptions about embodied difference, providers describe processes of unsettling the mythical norm of human embodiment common in health discourse/practice, coming to know disability in nonmedical ways, and re/discovering embodied differences and vulnerabilities. We argue that art-making produces instances of critical reflection wherein attitudes can shift, and new affective responses to difference can be made. Through self-reflective engagement with disability arts practices, providers come to recognize assumptions underlying health care practices and the vulnerability of their own embodied lives.